NATIONAL IDENTITY AS A TRANSLATION PROBLEM IN THE PROSE OF RUSSIAN AUTHORS OF THE LATE 20TH – EARLY 21ST CENTURIES - Nazarova Gulchehra Dovlatovna (Bright Mind Publishing, 2026)
National identity in the prose of Russian authors of the late 20th – early 21st centuries serves as a key component determining the specificity of the text and its cultural value. In translation, this element creates significant difficulties related to conveying culturally specific meanings, realia, concepts, and the author's idiostyle . The study identified the main problems of translating nationally marked units, trends toward semantic simplification and cultural adaptation, and demonstrated that preservation of identity is possible through flexible strategies balancing fidelity to the original and accessibility for the target-language reader.
Keywords: National identity, literary translation, Russian prose, culturally marked units, realia, ethnocultural concepts, translation strategies, domestication, foreignization, linguoculturology.